Водний режим у посівах соняшнику залежно від обробітку ґрунту та рівня мінерального живлення - Цилюрик, Олександр Іванович; Tsyliuryk, Аleksandr; Кохан, Андрій Володимирович; Kokhan, Andriy; Судак, Володимир Миколайович; Sudak, Volodymyr; Горбатенко, Андрій Іванович; Horbatenko, Andriy (Центр наукового запезпечення АПВ Харківської області, 2017)
Доведено високу ефективність мульчувального обробітку ґрунту (чизельне і плос- корізне розпушування) на фоні післяжнивних решток попередника (пшениця озима), які сприяють додатковому (45–113 м3/га) накопиченню продуктивної вологи в шарі 0–150 см, підвищенню рівня засвоєння опадів осінньо-зимового періоду до 45,4–47,8 %, більш еко- номному витрачанню води на створення одиниці сухої речовини урожаю та формуванню високої продуктивності соняшнику (2,53–2,72 т/га) порівняно з оранкою The level of the yield of sunflower largely depends on soil moisture reserves, which ensures the implementation of all essential life processes, including seed germination and seedling root, transpiration, thermoregulation and the supply of nutrients to the plant organism. Accumulation and rational use of soil moisture the most relevant in the steppe zone of insufficient moisture and unstable, where its total losses to runoff and evaporation unproductive reaches half the annual rainfall. With the high anthropogenic pressure water regime of soil may significantly deteriorate, so it is important to inventory accumulation of moisture at the bottom root layer (100–150 cm), where it gradually moves in an upward direction under the influence of gradients of different nature. 73 The purpose of research - to determine the effect of different ways of basic soil tillage and chemical fertilizers while abandonment stubble residues predecessor on the water regime and water consumption of sunflower crops, productivity and economic efficiency of cultivation in the conditions of northern Steppe of Ukraine. Research has established that for chiseling shaped micro undulating the ground and thick layer on the crests stubble contributed significantly reducing the wind speed in the surface layer. The snow was concentrated in the pits and was protected from blowing. Thanks to this snow depth here, to our knowledge, was the highest and amounted to – 16,3 cm. For chiseling cultivation presence of more snow and stubble limited distribution sub-zero temperatures in the soil profile, so that was smaller (on 5,4–8,2 cm) depth of soil freezing, thawing it faster and better accumulation of water. As a result, the intensity of moisture accumulation in the autumn-winter period when soil chiseling prevailed options plowing cultivation average of 11,3 mm. Elevated levels of assimilation rain cold period also associate the band thinning of the soil in the furrows, which is typical for this method. Against the backdrop of the involvement of stubble residues predecessor (winter wheat) and use chiseling. moldboardless mulch tillage promoted compared to plowing, additional (45– 113 m³/ha) accumulation of productive moisture in the layer 0–150 cm, raising the level of assimilation of rain fall and winter to 45,4–47,8 %, more economical consumption of water to create units of dry matter yield of sunflower (organo-mineral background). The use of the aforementioned methods of cultivation for mulch no fertilizers background and disking to any and all backgrounds have shaped the growth of consumption relative to control, because of the slower performance plants. Adding synthetic fertilizer, especially high nitrogen content (N60P30K30) contributed economical expenditure of water to create units of dry matter. More intense seasonal cycle of water on the background chiseling and moldboardless loosening the soil (over water use sunflower plants during the growing season and almost full compensation in the cold season) is considered as a positive factor which significantly activates the circulation of substances in the environment. At sites without making fertilizer (no fertilizer + stubble remains predecessor) better conditions for growth, development and formation of productivity of sunflower (2,35 tone/hectare) provides plowing, and the balanced organic-mineral background (N60P30K30 + stubble remains predecessor) – chiseling and moldboardless cultivation, which practically do not concede plowing and provide approximately the same seed yield (respectively 2,53–2,67; 2,57–2,72 and 2,51–2,64 tone/hectare). Minimization tillage of sunflower in makes it possible to improve the economic performance of oilseeds, namely to increase the profitability of production at 12–15 % and payback of 1 UAH production costs of 2,32 to 2,44–2,74 increase energy factor of 3,01 to 3,19–3,20 and save 12,3–13,8 liter/hectare fuel. On the basis of research, we can conclude that the use of mulch tillage (chiseling, moldboardless) against the backdrop of the involvement of stubble residues predecessor (winter wheat) contributes compared to plowing, additi-onal (45–113 m³/hectare) accumulation of productive moisture in the layer 0–150 cm, raising the level of assimilation of rain fall and winter period to 45,4–47,8 %, more economical consumption of water for the creation units of dry matter yield and high productivity of sunflower 2,53–2,72 tone/hectare.
Water regime in crops of sunflower depending on tillage of the soil and mineral nutrition
Keywords: соняшник; sunflower; мульчувальний обробіток ґрунту; mulch tillage; ґрунтова волога; soil moisture; післяжнивні рештки; stubble residue; добрива; fertilizers; урожайність; productivity